Equipping Students for the Real World: Using a Scaffolded Experiential Approach to Teach the Skill of Legal Drafting - Tammy Johnson; Francina Cantatore (Legal Education Review)
In spite of the growing number of formal mentoring programs aimed at facilitating the transition from law school studies to law practice, as well as evidence suggesting that law students need to proactively seek out and gain information and support from legal professionals, little empirical research examines mentoring as a source of professional and personal development among law school students. In order to address this gap in the literature, an independent law school1 located in the United States teamed up with one of its educational partners, a major university in the area,2 to undertake a qualitative study of the impact and effectiveness of mentoring on law students by lawyers. In particular, the researchers compared traditional mentoring, which they defined as involving a long-term relationship between one law student and one lawyer, and episodic mentoring, which they defined as one-time sessions between a law student and a lawyer which could be repeated by that law student with many different lawyers